Bosting of writing skill by using interactive venn diagram technique: Bosting of writing skill by using interactive venn diagram technique - Nanda Novia; Eli Nofriati (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2022)
The title of this research is “bosting of writing skill by using interactive venn diagrm technique (A lesson Study base at SMA 2 peusangan). The problem of the research is : How is the implementation of writing by using interactive venn diagram to second grade students of SMAN Peusangan through lesson study ? The purpose of the research is : To bosting students’ writing skill through the implementing interactive venn diagram technique to the second grade students of SMAN 2 Peusangan. Writing is generally considered the most difficult skill to learn, not only because of the need to master many English skills; reading, writing, and listening, but also because of the differences between the rules of the learner's mother tongue and the language being studied. There were some difficulties that students face during writing the descriptive paragraph. First, the problem in developing the ideas. Some students wrote many main ideas in one paragraph; the idea of the paragraph was still ambiguous. Sometimes, it is also found that some paragraphs were written in one sentence only, The idea of the paragraph was still not clear. Second, the problem in organizing the ideas to write a narrative text. Third, the students found difficulties in grammar. Third, the students found difficulties in grammar. Fourth, when students proceed writing something, many problems could be found, Some students are lack of vocabularies and they also have difficulties in developing their ideas related to their topic. The Fifth difficulty was students’ related with spelling, punctuation and capitalization. . Lesson Study is a study used by researchers with the aim of boosting students' writing skills with one or more technique in their class. The instruments used to collect the data are writing test and questionnaires. Based on the analysis of the students’ writing test, the researcher explained that the average persentage of the writing test is 49,33 %, the percentage showed that the problems are faced by students was from many aspect, such as : Feeling Crisis of IdeasIt is very difficult to start writing, for fear of being wrong/lack of confidence, or wanting the writing to be perfect immediately.